La experimentación como estrategia didáctica en la enseñanza- aprendizaje en las Ciencias Naturales en séptimo grado, Escuela Carlos Burneo Arias, periodo 2024-2025 - Caraguay Buri, Maria del Cisne (2025)
Currently, education faces significant challenges in incorporating teaching-learning strategies in the field of Natural Sciences. Therefore, the general objective of this research is to determine the importance of experimentation as a strategy to improve the teaching-learning process in Natural Sciences. The specific objectives considered the identification of experimental and practical teaching strategies employed by the teacher at the institution under study. Additionally, the research aimed to determine applicable experimental strategies and propose guidelines based on the experimental methodology as a didactic strategy. The research adopted a mixed approach, with a descriptive type and a non-experimental design, integrating methods such as scientific, statistical, descriptive, analytical, synthetic, deductive, inductive, and hermeneutic to examine both qualitative and quantitative data. The population consisted of one teacher and twelve seventh-grade students from the institution. The results of the interview with the teacher revealed a deficiency in the frequent use of experimental strategies, indicating that this lack is affecting the development of practical and meaningful learning in the students. Regarding the survey, 75% of the students reported not having conducted experiments, while 92% expressed interest in learning through experimental activities. This suggests that, although students show interest, there is no opportunity to teach through action-research processes, such as experimentation, which fosters long-lasting learning. Therefore, it is proposed to strengthen the teaching of Natural Sciences by connecting theory with practice in a motivating educational environment. It is concluded that there is a need to shift the educational approach through teacher training, adequate resources, and creative tools such as school gardens and experiments, promoting meaningful learning and the holistic development of students